GLOBAL SOUTH VERSUS GEOPOLITICAL SOUTH: A DEBATE ON THE ANALYTICAL RELEVANCE OF THE CONCEPTS - Costa, Hugo Bras Martins da; Duarte, Rubens de Siqueira (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2024)
The aim of this article is to analyze the limitations and analytical possibilities offered by the concepts of the Global South and the Geopolitical South for a more accurate understanding of the geopolitical dynamics of international relations in the first decades of the 21st century. In methodological terms, the article is based on an analysis of the history of the concept of the Global South, a critical reflection on the main shortcomings of its definition, a presentation of the concept of the Geopolitical South and, finally, a recognition of its main limitations, in order to indicate suggestions for improvement. In its conclusion, the article argues that the concept of the Geopolitical South generates greater analytical yield compared to the Global South due to its valorization of the agency of the countries of the South, the greater precision of its inclusion and exclusion criteria and its denunciation of the asymmetries and inequalities present in the North-South divide in international relations. However, we also argue that the Geopolitical South needs to be improved so that it is capable of simultaneously contemplating the dimension of the unity of the South, as a counterpoint to the North, the dimension of the diversity of the South, as an ontological phenomenon, and the dimension of change in terms of a state's affiliation to the Geopolitical South over time.